Comparison of patient outcomes between video and non-video laryngeal mask airway insertion performed by novices: a prospective randomized controlled study - Jiang, Ye; Xing, Fang; Wu, Qian; Gao, Yanan; Chen, Guozhong; Li, Cheng (Frontiers in Medicine, 2025)
ObjectiveThis study compares the patient outcomes of video laryngeal mask airway (V-LMA) and non-video laryngeal mask airway (NV-LMA) to assess which is easier for novices to master, achieves faster placement success, and causes least injury to the patients.MethodsTwenty novice practitioners (resident doctors/anesthesia nurses) from the Department of Anesthesia and Perioperative Medicine, Shanghai Fourth Peoples' Hospital, were randomized 1:1 to the V-LMA or NV-LMA group. After standardized training, the participants performed supervised LMA insertions on 60 patients. The learning outcomes and patient injury rates during LMA placement were compared between the groups.ResultsBoth groups achieved 100% first-attempt success. The V-LMA group demonstrated superior bronchoscope alignment (90% vs. 50%, P = 0.001). Postoperative throat pain was experienced by patients in both groups, but the V-LMA group demonstrated a lower 1-h incidence of postoperative throat pain (20% vs. 46.7%, P = 0.028), with better intraoperative hemodynamic stability.ConclusionWhen inserted by novice practitioners, the V-LMA improves placement accuracy and reduces patient injury compared with the NV-LMA.Clinical trial registrationChiCTR2300069399.